2020
DOI: 10.1061/(asce)gm.1943-5622.0001515
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Ballast Influenced by Deformation and Degradation: Laboratory Testing and Numerical Modeling

Abstract: This paper presents a study on the deformation and degradation responses of railway ballast using largescale laboratory testing and computational modeling approaches. A series of large-scale triaxial tests were carried out to investigate the ballast breakage responses under cyclic train loading subjected to varying frequencies, f=10-40 Hz. The role of recycled rubber energy-absorbing mats (REAMs) on reducing ballast breakage was also examined. Laboratory test results show that the ballast experiences significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Numerical modelling via the coupled DEM-FEM approach enables an insightful investigation of the mechanical response of ballast and how rubber mats reduce ballast breakage under cyclic loading, as also observed from laboratory tests using a large-scale cyclic triaxial equipment (Figure 7a) [74]. Ballast particles are modelled by bonding many disks with predetermined sizes together (Figure 7b), and ballast breakage is assumed to occur when those bonds are broken.…”
Section: Coupled Discrete-continuum Modelling (Dem-fem) For Ballasted Tracks With Rubber Matsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical modelling via the coupled DEM-FEM approach enables an insightful investigation of the mechanical response of ballast and how rubber mats reduce ballast breakage under cyclic loading, as also observed from laboratory tests using a large-scale cyclic triaxial equipment (Figure 7a) [74]. Ballast particles are modelled by bonding many disks with predetermined sizes together (Figure 7b), and ballast breakage is assumed to occur when those bonds are broken.…”
Section: Coupled Discrete-continuum Modelling (Dem-fem) For Ballasted Tracks With Rubber Matsmentioning
confidence: 99%
“…Data Availability Statement: The data presented in this study are openly available in reference number [38,74].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Regarding the ballast layer, its degradation can be associated with the abrasion between the corners of the aggregates or its crushing due to traffic overloads, along with ballast fouling, due to any fine particles that considerably affect water drainage, negatively influencing rail track stiffness regularity [19]. Aggregate degradation could be caused by climatic factors and freeze-thaw cycles [20], but mainly from the breaking of aggregates due to the passing traffic [21]. The variation in stiffness along the railway track induces a dynamic load between wheel-rail contact and sleeper-ballast, further increasing the fatigue problems in the rest of components [22], while also varying the bearing capacity of the track.…”
Section: Component Fatigue Failurementioning
confidence: 99%
“…The economic analyses of Wheat and Smith [4] based on UK rail systems found that more than one-third of the overall capital cost on all ballasted rail networks corresponds to the track substructure. As a consequence of severe ballast deterioration, the Australian rail sector invests a massive amount on regular track rehabilitation (e.g., over AUD 12 million per annum in the state of New South Wales alone), and substantial land development before track construction, where poor and deteriorated base soils (subgrade) provide significant challenges [5]. For this reason, numerous research studies have been conducted to address the challenges of increasing demand for higher performance track substructure, and thereby to effectively manage the growing need for high-speed commuter lines as well as higher axle heavy haul railways [6,7].…”
Section: Introductionmentioning
confidence: 99%